2003
DOI: 10.2169/internalmedicine.42.888
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Acute Pancreatitis with Cystic Formation in Reactive Systemic AA Amyloidosis Secondary to Rheumatoid Arthritis

Abstract: Wereport a patient with reactive systemic AAamyloidosis secondary to rheumatoid arthritis who showed fatal acute pancreatitis with a cystic formation in the pancreas head. The pancreatitis rapidly worsened despite intensive treatment and resulted in death. In this patient severe deposition of amyloid in the gastrointestinal tract was considered to play an important role in the pathogenesis of the acute pancreatitis. This is an unusual complication in patients with AAamyloidosis, but we should consider it as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Both hemorrhage and inflammatory changes were regarded as secondary to amyloidosis due to the chemoattractant features of serum amyloid AA and increased vascular permeability. Similar to the present finding, acute pancreatitis has also been reported as a rare complication of generalized amyloidosis in human beings and it has been demonstrated that this complication might be fatal because generalized amyloidosis usually involves dysfunction in multiple organs (Matsuda et al, 2003). Although the question remains open as to the cause of adhesions in the intra-abdominal organs, there is, however, little doubt that chronic inflammation and altered vascular permeability give rise to serosal adhesions.…”
supporting
confidence: 88%
“…Both hemorrhage and inflammatory changes were regarded as secondary to amyloidosis due to the chemoattractant features of serum amyloid AA and increased vascular permeability. Similar to the present finding, acute pancreatitis has also been reported as a rare complication of generalized amyloidosis in human beings and it has been demonstrated that this complication might be fatal because generalized amyloidosis usually involves dysfunction in multiple organs (Matsuda et al, 2003). Although the question remains open as to the cause of adhesions in the intra-abdominal organs, there is, however, little doubt that chronic inflammation and altered vascular permeability give rise to serosal adhesions.…”
supporting
confidence: 88%
“…Severe AAa may involve blood vessels of different calibers of the pancreas and should be regarded as important factors in the pathogenesis of aRelLnP [74]. The role of severe AAa in pathogenesis of fatal acute pancreatitis is confirmed by others as well [75][76][77].…”
Section: Discussionmentioning
confidence: 86%
“…In the present patient, systemic amyloidosis might have led to a more severe and aggressive attack of pancreatitis. In fact, perivascular amyloid deposit with pancreatic ischemia and circulatory impairment as well as amyloidosis-related deformity of the duodenal papilla and pancreatic and biliary ducts are proposed as possible mechanisms for pancreatitis in patients with systemic amyloidosis (4-6). As an example, a fatal acute pancreatitis has been reported in a patient with rheumatoid arthritis and secondary systemic AA amyloidosis (4).…”
mentioning
confidence: 99%